MANAJEMEN PEMELIHARAAN TERNAK SAPI POTONG DI TINGKAT PETERNAKAN RAKYAT DI WILAYAH AGROEKOSISTEM LAHAN KERING - budi utomo (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2022)
The research was conducted in 2018, in the dry land agro-ecosystem area, namely in Karangharjo Village, Sulang District, Rembang Regency. The aim of the study was to determine the reproductive picture (Service per conception S/C, post partus unestrus (APP), calving interval) of beef cattle in a traditional farming system at the level of smallholder farming. The research method uses descriptive methods and data obtained through surveys with interviews with 30 respondents and using a structured list of questions as a tool to collect the necessary data. The data obtained were then described and interpreted. The results showed that the breeds of cattle kept by breeders were the Ongole (PO) breeds and the breeds of Simmental and PO (Simpo) crosses. The average ownership of PO cattle is between 2-3 heads and the Simpo cattle breed is on average 1-2 heads. The forage provided from November to March was mostly grass and some superior grass, but the forage provided from April to October consisted of grass, sugarcane shoots and rice straw. Not all breeders provide additional feed in the form of rice bran to their livestock. There are differences in post partum unestrus (APP), service per conception and calving interval between cattle fed with supplementary feed and without additional feed, both PO and Simpo cattle. However, there was no difference between PO cattle and the age at first mating, as well as between Simpo cattle, but the first mating age for PO cattle was faster than Simpo cattle.Keywords: Beef cattle, feed and reproduction